Evaluación de benzoato de estradiol y cipionato de estradiol en vacas cebuinas receptoras de embriones sobre los parámetros reproductivos. - Cool Loor, Juan Pablo (2017)
The main goal of this research project was to evaluate two types of estrogens on reproductive parameters in Zebu cows receiving embryos. Estradiol Cypionate (0.5 mg) and estradiol Benzoate (1 mg) were studied. The first treatment had 48 individuals and the second 45. both treatments 400 IU of equine chorionic hormone (ECG) it was applied along with PGF2α. Utilization rate (%), pregnancy rate (%) and ovulation rate (%) were evaluated, and the economic analysis of the protocols was performed. The date were assessed using Chi square and confidence interval. The results indicate that the variables studied showed no difference (p> 0.05) according to Chi square analysis. However, when analyzing pregnancy rates, the use of estradiol benzoate reached the highest value with 51.1 % as opposed to the cypionate which obtained 39.6%. In the other variables, no significant differences were found since similar conditions were maintained between treatments. The analysis of the economic cost per treatment was also carried out and the protocol in which Estradiol Benzoate was used was more economical in linking it with the efficiency of the pregnancy method. Due to this advantage, the use of benzoate estradiol in mixed zebu cows in protocols where embryo transfer is performed.